EVALUASI PROGRAM DESA MEKARSARI - Bustamin Abidin, Sujianto, Febri Yuliani (JIANA ( Jurnal Ilmu Administrasi Negara ), 2020)
Evaluation, Mekarsari Village Program. This study aims to find out the evaluation of the Mekarsari Village Program, Reteh District, Indragiri Hilir District 2016 The method used in this study is a qualitative descriptive method. The research informants are the village head, secre-tary, treasurer, BPD chairman, village assistant, community leader. Data collection techniques through interviews, observation of documentation. Data analysis techniques in this study used qualitative research methods consisting of data reduction, data presentation and conclusion draw-ing. The results of this study indicate that the village government of MEKARSARI has carried out several activities in the Village Administration, Village Development, Community Development and Community Empowerment programs. In carrying out these activities the researcher evaluates whether the activities have been carried out optimally according to the policies that have been formulated, but several obstacles are still encountered, namely the factor of limited funds because of funding sources, human resources, and at the time of implementation of some location points difficult to reach due to geographical conditions location area.